Electrical Properties of GaN/Ga2O3 P-N Junction Diodes: A TCAD Study - Duyen-Thi Nguyen; Khanh Nguyen; Duc-Minh Truong; Huy-Binh Do (Journal of Technical Education Science, 2024)
Ga2O3 and GaN are promising candidates for the fabrication of high power semiconductor devices due to their wide band-gap range, deteremined from 3.0 eV to 4.9 eV. Among these materials, the GaN/Ga2O3 P-N junction diode has an excellent performance even at high temperatures, making it suitable for high-power applications. In this work, GaN/Ga2O3 P-N junction diodes are investigated using computer-aided design (TCAD) simulations. The properties of the diode were optimized in terms of the thickness of the p-type GaN layer and its doping concentration. It was found that the current-voltage (IV) characteristic of the diode decreases as the thickness of GaN layer increases. To achieve a high current output, the optimized thickness is determined to be 500 nm. Furthermore, the doping concentration within the diode strongly influences the output current. The highest current is obtained for an un-doped GaN sample, and the increase in the doping concentration leads to a decrease in the obtained current.